Excel 2016 for Marketing Statistics A Guide to Solving Practical Problems - Quirk, Thomas J.; Rhiney, Eric (Excel for Statistics, 2016)
This is the first book to show the capabilities of Microsoft Excel in teaching marketing statistics effectively. It is a step-by-step exercise-driven guide for students and practitioners who need to master Excel to solve practical marketing problems. If understanding statistics isn't your strongest suit, you are not especially mathematically-inclined, or if you are wary of computers, this is the right book for you. Excel, a widely available computer program for students and managers, is also an effective teaching and learning tool for quantitative analyses in marketing courses. Its powerful computational ability and graphical functions make learning statistics much easier than in years past. However, Excel 2016 for Marketing Statistics: A Guide to Solving Practical Problems is the first book to capitalize on these improvements by teaching students and managers how to apply Excel to statistical techniques necessary in their courses and work. Each chapter explains statistical formulas and directs the reader to use Excel commands to solve specific, easy-to-understand marketing problems. Practice problems are provided at the end of each chapter with their solutions in an appendix. Separately, there is a full Practice Test (with answers in an Appendix) that allows readers to test what they have learned. Includes 167 illustrations in color Suitable for undergraduates or graduate students Prof. Tom Quirk spent six years in educational research at The American Institutes for Research and Educational Testing Service.  He is Professor of Marketing in the Walker School of Business & Technology at Webster University in St. Louis, Missouri (USA).  He holds a B.S. in Mathematics from John Carroll University, both an M.A. in Education and a Ph.D. in Educational Psychology from Stanford University, and an MBA from The University of Missouri-St. Louis. Prof. Eric Rhiney is currently an Assistant Professor of Marketing in The Walker School of Business at Webster University in St. Louis, Missouri (US) where he teaches Research Design, Marketing Research and Marketing Strategies.  He holds a B.S.B.A. with an Emphasis in Marketing from University of Central Missouri, an M.B.A. with an Emphasis in Marketing from Webster University, and a Ph.D. in Marketing and International Business from St. Louis University.  He did marketing research professionally for over ten years engaging in research for companies such as Pizza Hut, Monsanto, Chrysler and Hardee's.  He is involved in a number of quantitative research studies focused on in-group out-group orientation on consumer attitudes, digital marketing behavior, and cross-cultural marketing and has presented is work at a number of conferences including The American Marketing Association, the International Business Association, and the Marketing Management Association and the University of Missouri-St. Louis (UMSL) Digital Marketing Conference.